Obstetric complications during childbirth in adolescents treated in a high Andean hospital in Peru - Ataypoma-Meneses, Rocio Elendia (2024)
Objectives: Determine obstetric complications during childbirth in adolescents treated at an Altoandino Hospital in 2022. Material and method: Descriptive, observational, retrospective and cross-sectional. The sample consisted of 39 adolescents who presented complications in the three periods of childbirth. A data collection form and the documentary analysis technique were used, and the data were processed with the statistical program IBM SPSS Statistics for Windows Version 28.0. Results: During the effacement and dilation period, complications included: 23.1% premature rupture of membranes, 20.5% prolonged labor, 15.4% preeclampsia, 10.3% cephalopelvic disproportion, 7.7% childbirth prolonged and 2.6% cephalopelvic disproportion. During the expulsion period, the complications observed were: 10.3% shoulder dystocia and tears, 5.1% problems with the umbilical cord and 2.6% shoulder dystocia and prolonged expulsion. Furthermore, 5.1% presented retention of placental remains during the delivery period. Conclusion: It was determined that complications occurred more frequently during the dilation and effacement period.